Effect of molybdenum on the formation of Ti6Si2B in mechanically alloyed Ti-Mo-Si-B powders - Nunes, Perseu Amaral; Ramos, Alfeu Saraiva [UNESP]; Trindade Ramos, Erika Coaglia (Trans Tech Publications, 2012)
This paper discusses on effect of molybdenum on the Ti6Si2B formation in mechanically alloyed and hot-pressed Ti-xMo-22Si-11B (x= 2, 5, 7 and 10 at%) alloys. High-energy ball milling and hot pressing were utilized to produce homogeneous and dense materials, which were characterized by scanning electron microscopy, X-ray diffraction, electron dispersive spectrometry, and Vickers hardness. The excessive agglomeration during milling was more pronounced in Moricher powders, which was minimized with the formation of brittle phases. Hot pressing of mechanically alloyed Ti-xMo-22Si-11B powders produced dense samples containing lower pore amounts than 1%. Ti6Si2B was formed in microstructure of the hot-pressed Ti-2Mo-22Si-11B alloy only. In Mo-richer quaternary alloys, the Ti3Si and Ti5Si3 phases were preferentially formed during hot pressing. Oppositely to the ternary phase, the Ti3Si phase dissolved a significant Mo amount. Vickers hardness values were reduced in hot-pressed Ti-xMo-22Si-11B alloys containing larger Mo amounts, which were dissolved preferentially in Ti solid solution. © (2012) Trans Tech Publications, Switzerland.
Keywords: High-energy ball milling; Hot pressing; Titanium alloy; Dense materials; Mechanically alloyed; Quaternary alloys; Ternary phase; Alloys; Ball milling; Molybdenum; Molybdenum alloys; Powders; Scanning electron microscopy; Silicon; X ray diffraction; Titanium alloys